2003
DOI: 10.1021/ja034583z
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Design for Multivalent Interaction:  Maltose Mobility along Polyrotaxane Enhanced Binding with Concanavalin A

Abstract: High molecular mobility of maltose-conjugated alpha-cyclodextrins (alpha-CDs) along a poly(ethylene glycol) (PEG) chain due to the mechanically locked structure of polyrotaxanes enhanced multivalent interactions between maltose and concanavalin A (Con A). When maltose groups are conjugated with alpha-CDs that were threaded onto a PEG capped with benzyloxycarbonyl l-tyrosine (polyrotaxane), Con A-induced hemagglutination was greatly inhibited by polyrotaxanes with a certain threading % of alpha-CDs. Such an inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
183
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(184 citation statements)
references
References 21 publications
1
183
0
Order By: Relevance
“…[1][2][3] They possess a necklace-like molecular structure in which two bulky groups are attached to each polymer terminal so that the dissociation of the CD molecules is prevented. With the intriguing characteristics of free sliding and/or rotating of the threaded cyclic molecules, the polyrotaxanes have attracted increasing interests for their potential applications in smart materials, for example, stimuliresponsible supramolecular hydrogels, 4 slide-ring gels, 5,6 molecular machines, 7 carriers for drug delivery with hydrolysable bulky ends, 8 energy-transfer systems with modified CDs, 9 pH-/temperature-sensitive supramolecular micelles 10 and insulated molecular wires. 11 As for their preparation, a wide variety of strategies have been developed, [12][13][14] with a number of bulky groups such as naphthyl, 15 trinitrophenyl, 16 fluorescein-4-isothiocyanate 17 and 9-anthryl groups as the end stoppers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] They possess a necklace-like molecular structure in which two bulky groups are attached to each polymer terminal so that the dissociation of the CD molecules is prevented. With the intriguing characteristics of free sliding and/or rotating of the threaded cyclic molecules, the polyrotaxanes have attracted increasing interests for their potential applications in smart materials, for example, stimuliresponsible supramolecular hydrogels, 4 slide-ring gels, 5,6 molecular machines, 7 carriers for drug delivery with hydrolysable bulky ends, 8 energy-transfer systems with modified CDs, 9 pH-/temperature-sensitive supramolecular micelles 10 and insulated molecular wires. 11 As for their preparation, a wide variety of strategies have been developed, [12][13][14] with a number of bulky groups such as naphthyl, 15 trinitrophenyl, 16 fluorescein-4-isothiocyanate 17 and 9-anthryl groups as the end stoppers.…”
Section: Introductionmentioning
confidence: 99%
“…Among these systems, DMSO is one of the most popular and the most investigated solvents for polyrotaxane. Aprotic and neutral DMSO readily dissolves PEG/CD polyrotaxane to yield a polyrotaxane solution in which many reactions and/or modifications have been made to date [10,[13][14][15][16]22]. However, many unrevealed properties seem to be potentially buried within this solution system.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the inclusion complex with CDs and various linear polymers via spontaneous self-assembly was thoroughly investigated by Harada et al [1,5,6], who successfully prepared polyrotaxane by binding bulky end groups (such as dinitrophenyl moieties) to the ends of pseudopolyrotaxane, i.e., the inclusion complex of CDs and PEG [7][8][9]. A wide variety of attractive concepts have been reported to date after the first finding by Harada, such as the preparation of a "molecular tube" by cross-linking adjacent CDs in single polyrotaxane followed by the dissociation of the included PEG [10], an insulated molecular wire comprising a conducting polymer and a molecular tube [11,12], a drug delivery system using polyrotaxane carrying drugs on the CD moiety [13], multivalent ligand system [14], the construction of an energy transfer system using polyrotaxane with photoluminescent side groups [15,16], a three-dimensionally cross-linked polyrotaxane network [17][18][19] and fiber formation by the wet spinning of a blend solution of polyrotaxane and cellulose [20].Since further applications of polyrotaxane than that mentioned above are anticipated in the future, the fundamental properties of polyrotaxane should be thoroughly characterized. Solution property is one of the most significant characteristics, which is necessary during processing and handling polyrotaxane when used in various applications.…”
mentioning
confidence: 99%
“…4,5 Molecular weight changes affect the physical properties of the polymers such as mobility, 20,21 and the low molecular weight polymers had better mobility. It has been reported that glycopolymer with better mobility showed better binding properties to the target protein, 22 and so the greater mobility could contribute to the better binding. In addition, we fixed the concentration of sugars in the experiments, and the number of the molecules was different.…”
mentioning
confidence: 99%